2013
DOI: 10.18542/amazonica.v5i1.1295
|View full text |Cite
|
Sign up to set email alerts
|

Anemia Falciforme Como Experiência: Relações Entre Vulnerabilidade Social E Corpo Doente Enquanto Fenômeno Biocultural No Estado Do Pará

Abstract: Sickle Cell Anemia (SCA) is a chronic, hereditary disease with high prevalence among people of African descent in Brazil. There are few studies about the reality of the affected individuals in the Amazon. SCA can be considered a biocultural disease as it involves evolutionary, genetic, environmental socioeconomic and cultural aspects which influence the daily living of the patients. This qualitative, ethnographic research was conducted with a sample of 40 individuals HB*SS -or their parents, when children -fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
5
0
4
Order By: Relevance
“…According to the authors low income, poor schooling, lack of a fix salary and job instability contribute to increase vulnerability that leads to low pay or unemployment in adult life. Silva et al (2013) emphasized that low income resulted from the lack of qualification of the SCD population, who cannot compete for a position in the job market in order to improve their life quality. However, when they get a job, their absenteeism is high due to the frequent pain crisis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the authors low income, poor schooling, lack of a fix salary and job instability contribute to increase vulnerability that leads to low pay or unemployment in adult life. Silva et al (2013) emphasized that low income resulted from the lack of qualification of the SCD population, who cannot compete for a position in the job market in order to improve their life quality. However, when they get a job, their absenteeism is high due to the frequent pain crisis.…”
Section: Resultsmentioning
confidence: 99%
“…According to Silva et al (2013), pain is the recurrent symptom of SCD and the most bothersome for it limits working activities as well as social, affective, sexual and family relations directly affecting life quality. Ohara et al (2012) found that pain is felt mainly in the hips and lower limbs followed by the dorsal and lumbar region and arms.…”
Section: Resultsmentioning
confidence: 99%
“…Os fatores adquiridos ou ambientais, além dos hereditários, exercem importante influência nas consequências fisiopatológicas no curso da AF. De maneira geral, o nível socioeconômico e educacional ocupa posição de destaque ao determinar variantes como acesso à atenção médica e melhores condições de moradia e trabalho (18) , com proporcional qualidade de vida. No entanto, estudo realizado em Uberaba, Minas Gerais, com 47 portadores de AF de hemocentro regional e de indivíduos com AF evidenciou elevação no nível de escolaridade, com o ensino médio completo em quase 43% dos pacientes.…”
Section: Discussionunclassified
“…Nesta pesquisa mais da metade dos usuários do ambulatório residia em casas de alvenaria, com saneamento básico pela rede pública em quase 90% das moradias, encontrou-se então cenário que contribui para melhor prognóstico dos pacientes. Esta informação é importante, pois águas contaminadas por nitritos e micro-organismos provenientes de dejetos humanos e animais são fatores que convergem para acentuar a morbimortalidade dessa clientela (16) , segundo a literatura há maior suscetibilidade para destruição precoce dos eritrócitos em ambientes com gases poluentes, alimentos e água contaminados por nitritos (16,18) . Em outro aspecto, o diagnóstico realizado antes de completar o primeiro ano de vida decorre da política pública de saúde brasileira instituída no âmbito do SUS, desde 2001, na qual o "Teste do Pezinho" permite diagnóstico das hemoglobinopatias dos recém-nascidos (11)(12)(13) .…”
Section: Discussionunclassified
“…This work will be of value when it identifies the pathways and structural mechanisms by which racism has its impacts. Once that has been accomplished, it will be a matter of political will to target these pathways and mechanisms for intervention 11 (Jones 2003: 09 O insulto a uma pessoa fragilizada por uma doença é um indício para o enredamento de sua fragilidade, objeto de artigos e debates em torno da vulnerabilidade da DF, contudo, grande parte das pessoas que convivem com o episódio, geralmente, costumam lidar com o problema de modo a se isolar socialmente, causando nelas um transtorno psicossocial (Silva 2013;Buss e Filho 2007;De Marco 2006;Batista 2008;Naoum 2000a). Abaixo os interlocutores discorrem sobre o seu estado psicossocial:…”
Section: Referenciais E Discussãounclassified